Pan-Immune-Inflammation Value and Risk of Hypertensive Disorders of Pregnancy: A Cross-Sectional Study - Yin S; Wan H; Zhang Y; Zhu M; Wang Z; Cui Z (Journal of Inflammation Research)
Shengting Yin,1 Huimin Wan,1 Yanhua Zhang,1 Mengchu Zhu,2 Zhenwei Wang,3 Zhenghui Cui1 1Department of Obstetrics, Women’s Hospital, Zhejiang University School of Medicine, Hangzhou, 310006, People’s Republic of China; 2Department of In-Vitro Fertilization Laboratory, Women’s Hospital, Zhejiang University School of Medicine, Hangzhou, 310006, People’s Republic of China; 3Department of Cardiology, the First Affiliated Hospital of Zhengzhou University, Zhengzhou, 450000, People’s Republic of ChinaCorrespondence: Zhenwei Wang, Department of Cardiology, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, 450000, People’s Republic of China, Email 1229445463@qq.com Zhenghui Cui, Department of Obstetrics, Women’s Hospital, Zhejiang University School of Medicine, Hangzhou, 310006, People’s Republic of China, Email 5514001@zju.edu.cnObjective: This research sought to investigate the connection between pan-immune-inflammation value (PIV) and hypertensive disorders of pregnancy (HDP).Methods: This retrospective cross-sectional study included 1002 pregnant women who delivered in Women’s Hospital, Zhejiang University School of Medicine from January to February 2024.Their basic information and laboratory values during the second trimester (24– 28 weeks of gestation) were collected from medical records and the hospital information management system, and PIV values were calculated. We explored the relationship between PIV and the risk of developing HDP via univariate and multivariate logistic regression analyses. Receiver operating characteristic (ROC) curve analysis was used to evaluate the ability of PIV to predict the risk of developing HDP. Since preeclampsia (PE) is an important disease of HDP, we also explored the relationship between PIV and the risk of developing PE.Results: Patients with HDP presented higher PIV levels (P < 0.001). PIV, a risk factor, was significantly associated with HDP and PE according to the univariate regression analysis (P < 0.001). Even after adjusting for potential confounding factors, the risk of developing HDP and PE remained significantly greater. According to subgroup analysis, PIV was significantly and positively associated with the development of HDP and PE among pregnant women aged < 35 years and with normal pre-pregnancy body mass index (P < 0.05). ROC curve analyses indicated that PIV had a high predictive value for both HDP and PE (P < 0.001).Conclusion: Increased PIV levels are associated with a greater risk of developing HDP and PE, suggesting that PIV is an independent risk factor for the development of HDP and PE.Keywords: pan-immune-inflammation value, hypertensive disorders of pregnancy, preeclampsia, risk, receiver operating characteristic